Molecular Confirmation of Salmonella typhimuriumin Poultry from Kathmandu Valley - Adhikari, Sanjeev Kumar; Gyawali, Arrogya; Shrestha, Sajan; Shrestha, Swoyam Prakash; Prajapati, Meera; Khanal, Doj Raj (Journal of Nepal Agricultural Research Council, 2018)
A prevalence study was carried to isolate Salmonella typhimurium from blood (n= 50) and gut samples (n=100) of poultry in Kathmandu valley during early 2016. Salmonella typhimurium bacteria isolated in the selective media were biochemically confirmed based on Bergey’s Manual. Two sets of oligonucleotide primers-the genus specific 16S rRNA and the organism specific invA were employed for molecular level confirmation by the Polymerase Chain Reaction (PCR) assay. The amplified fragments in 1% agarose gel observed at 406bp and 285bp, respectively confirmed the isolates to be Salmonella typhimurium. Of 150 samples tested, Salmonella typhimurium were isolated from 49 samples, among which nine were from blood (18%) and forty from the gut (40%). The present result indicated an alarmingly high level of Salmonella typhimurium, which can result inzoonotic infection in humans owing to increased contact with poultry and consumption of poultry products in the Kathmandu valley.